2021
DOI: 10.3389/fimmu.2020.616367
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Deprivation Promotes the Generation and Mobilization of MDSCs by Enhancing Expression of G-CSF and GM-CSF

Abstract: Solid tumors are often challenged by hypoxic and nutrient-deprived tumor microenvironments (TME) as tumors progress, due to limited perfusion and rapid nutrient consumption. While cancer cells can demonstrate the ability to survive in nutrient-deprived conditions through multiple intrinsic alterations, it is poorly understood how nutrient-deprived cancer cells co-opt the TME to promote cancer cell survival and tumor progression. In the present study, we found that glutamine deprivation markedly potentiated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…Metabolically reprogrammed tumor cells compete with immune cells for nutrients and release metabolites into the microenvironment, which inhibit the function of antitumor immune cells; thus, blocking the abnormal metabolism of tumor cells may be a potential way to improve the efficacy of immunotherapy. Previous studies have reported that in breast cancer, glutamine metabolism alterations increased the secretion of G-CSF and GM-CSF, then recruited MDSC to promote tumor progression [ 39 ]. The enhanced glutamine uptake influenced the composition of the immune cell infiltrates and was significantly associated with upregulated PDL1 expression as well as poor survival outcomes in breast cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically reprogrammed tumor cells compete with immune cells for nutrients and release metabolites into the microenvironment, which inhibit the function of antitumor immune cells; thus, blocking the abnormal metabolism of tumor cells may be a potential way to improve the efficacy of immunotherapy. Previous studies have reported that in breast cancer, glutamine metabolism alterations increased the secretion of G-CSF and GM-CSF, then recruited MDSC to promote tumor progression [ 39 ]. The enhanced glutamine uptake influenced the composition of the immune cell infiltrates and was significantly associated with upregulated PDL1 expression as well as poor survival outcomes in breast cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low glutamine levels may affect the differentiation of MDSCs and contribute to these expanded populations in severe COVID-19, but the experimental results are inconsistent. Some studies reported that low glutamine inhibited the differentiation of MDSCs [ 84 , 85 ], while others revealed that glutamine deprivation promoted the generation of MDSCs [ 86 ]. In a murine arthritis model, the inhibition of glutaminolysis suppressed the differentiation of M-MDSCs, but promoted the expansion of G-MDSCs [ 87 ].…”
Section: Consequences Of Glutamine Deficiency and Covid-19mentioning
confidence: 99%
“…However, whether they can achieve similar efficacy in renal fibrosis remains unclear. A recent study has reported that enhanced G-CSF and GM-CSF expression promotes MDSC generation and migration (12,44), indicating that G-CSF and GM-CSF are both efficient for inducing MDSC expansion. However, although G-CSF is more commonly used in clinical settings, GM-CSF is well accepted for in vitro MDSC induction because it can induce both MDSC phenotypes (CD11b + Ly6G i n t Ly6C l o w and CD11b + Ly6G i n t Ly6C l o w populations) in a balanced manner.…”
Section: Discussionmentioning
confidence: 99%